Alterations in functional connectivity of the anterior cingulate cortex associated with different levels of tau and amyloid-β deposition in patients with mild cognitive impairment - Qi, Wenzhang; Ruan, Yiming; Tang, Yue; Zheng, Darui; Yuan, Qianqian; Xue, Chen; Xiao, Chaoyong (Frontiers in Neuroscience, 2026)
BackgroundThree subgroups of mild cognitive impairment (MCI) may be identified based on the deposition of Aβ and tau proteins: A-T-, A + T+, and A + T-. The key hub for information processing and control, the anterior cingulate cortex (ACC), is essential for both healthy aging and MCI. The objective of this research is to systematically investigate changes in the functional connectivity (FC) of ACC subregions across different MCI subtypes.MethodsOverall, 54 A-T- patients, 28 A + T- patients, and 52 A + T + patients underwent FC analysis of ACC subregions. Correlation analyses were conducted to explore the relationship among pathological biomarkers, cognitive function, and FC changes in ACC subnetworks. The diagnostic utility of ACC-cortical FC in differentiating MCI subtypes was evaluated using receiver operating characteristic (ROC) curves.ResultsCompared with the A-T- group, the A + T- group demonstrated reduced FC in the right precuneus and left dorsal ACC, whereas the A + T + group demonstrated increased FC in the left hippocampus, right precuneus and left dorsal ACC, the left superior frontal gyrus and right subgenual ACC. Compared with the A + T- group, the A + T + group demonstrated increased FC in the right precuneus and left dorsal ACC. The altered FC in ACC subnetworks was significantly correlated with pathological biomarkers in the cerebrospinal fluid. The ROC curve analysis suggested that changes in ACC FC effectively distinguished between the various pathological subtypes of MCI.ConclusionIn summary, different MCI subtypes have distinctive changes in the FC of ACC subregions, providing valuable insights into the mechanisms underlying MCI.